2016
DOI: 10.1534/g3.116.027961
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Drosophila Somatic Gene Expression: Variation and Regulation by doublesex

Abstract: Sex differences in gene expression have been widely studied in Drosophila melanogaster. Sex differences vary across strains, but many molecular studies focus on only a single strain, or on genes that show sexually dimorphic expression in many strains. How extensive variability is and whether this variability occurs among genes regulated by sex determination hierarchy terminal transcription factors is unknown. To address these questions, we examine differences in sexually dimorphic gene expression between two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 66 publications
(123 reference statements)
6
35
0
Order By: Relevance
“…dsx encodes transcription factors involved in the establishment of almost all morphological traits that differ between males and females (Baker and Ridge, 1980;Hildreth, 1965). The Dsx M and Dsx F proteins share a common DNA-binding domain and bind to the same target sequences, but have different and sometimes opposite effects on gene expression, leading to sex-specific cell differentiation (Arbeitman et al, 2004(Arbeitman et al, , 2016Burtis et al, 1991;Goldman and Arbeitman, 2007;Lebo et al, 2009;Li and Baker, 1998;Yang et al, 2008). For instance, the Yolk protein 1, bric a brac, Fmo-2 and Fad2 genes are directly regulated by Dsx and are expressed at higher levels in females compared with males.…”
Section: Introductionmentioning
confidence: 99%
“…dsx encodes transcription factors involved in the establishment of almost all morphological traits that differ between males and females (Baker and Ridge, 1980;Hildreth, 1965). The Dsx M and Dsx F proteins share a common DNA-binding domain and bind to the same target sequences, but have different and sometimes opposite effects on gene expression, leading to sex-specific cell differentiation (Arbeitman et al, 2004(Arbeitman et al, , 2016Burtis et al, 1991;Goldman and Arbeitman, 2007;Lebo et al, 2009;Li and Baker, 1998;Yang et al, 2008). For instance, the Yolk protein 1, bric a brac, Fmo-2 and Fad2 genes are directly regulated by Dsx and are expressed at higher levels in females compared with males.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a few other DSX targets have been identified, including the bric a brac locus (bab1 and bab2), which regulates sex-specific abdominal pigmentation (Williams et al, 2008). In addition, genomic studies have predicted many more DSX targets (Chatterjee et al, 2011;Luo et al, 2011;Clough et al, 2014;Arbeitman et al, 2016) In Drosophila, both the ovary and testis have germline stem cells (GSCs) that are controlled and maintained by surrounding somatic cells. A key component of the male stem cell niche is created by the 'hub', a tight cluster of cells at the anterior tip of the testis (Aboïm, 1945;Hardy et al, 1979;Kiger et al, 2000;Tulina and Matunis, 2001), which forms during the last stages of embryogenesis (stage 17) (Gönczy et al, 1992;Le Bras and Van Doren, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, we cannot exclude that there are minor changes or changes in a subset of neurons that would be missed by our approach. Likewise, this result can depend on the specific wt strain used for the analysis as it has been shown that sex-specific expression can vary significantly between different wt strains [Arbeitman et al, 2016]. In summary, however, the results of our RNA-Seq analysis demonstrate that sex-specific AS in the head appears to be rather independent of the germline or the mating process.…”
Section: Adult Sex-specific As Is Independent Of the Germline And Matmentioning
confidence: 58%